PENGARUH KOMPOS AMPAS TEBU (Saccharum officinarum L.) TERHADAP PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescent L.) - Sri Ningsih; Nusyirwan Nusyirwan; Nusyirwan Nusyirwan (JBIO: jurnal biosains (the journal of biosciences), 2018)
This study aims to determine the effect of bagasse compost administration on the growth of Capsicum frutescent L. Parameters used were C / N ratio, plant height, number of leaves, leaf area, time of flower appearance, number of flowers, number of primary branches, number of fruits, root length. This study used a Completely Randomized Design (CRD), and the treatment was arranged in 5 treatments and repetitions five times. The first factor is the dose of organic fertilizer, namely A (0 grams), treatment B (150 grams), treatment C (200 grams), treatment D (250 grams), treatment E (300 grams). The variance homogeneity test can be done using SPSS 21 program. The results of the study on plant height were in treatment E (dose of 300 grams) which is 50.2 cm. The highest number of leaves obtained in treatment B (dose 150 grams) is 22.4 strands. The highest leaf area is found in treatment E (dose of 300 grams) which is 41.4 cm2. The highest number of branches is found in treatment A (dose of 0 grams), which is 4. For the time the flower appears on this cayenne plant on average at six weeks after planting (MST). The highest amount of interest is found in treatment E (dosage of 300 grams) which is 7.4 flowers. The highest amount of fruit in treatment E (dose of 300 grams) is four pieces. While the longest root size found in treatment E (dose of 300 grams) is 4.78 cm. This research is expected to be valuable information in the use of bagasse (Saccharum officinarum L.) on the cultivation of cayenne pepper (C. frutescent L.)